-7x+7x+6x=

Simple and best practice solution for -7x+7x+6x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x+7x+6x= equation:


Simplifying
-7x + 7x + 6x = 0

Combine like terms: -7x + 7x = 0
0 + 6x = 0
6x = 0

Solving
6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '6'.
x = 0

Simplifying
x = 0

See similar equations:

| m-2m-3m+4= | | g^3+3g^2-1g-3=0 | | -3p+40=-2p-10 | | -3p+40=-2-10 | | 8*16-2y=90 | | 7x+14=9x+18 | | -(3y+5)-(-2y-6)=0 | | 16=3(3x) | | 3(x+2)=2(x-1) | | 3x^2-30x+3=0 | | 9-5(x-2)=22 | | 4a^2=100 | | -(4y+4)-(-3y-5)=-4 | | -5+x=-15 | | 0.16(6)+0.04x=0.08(18+x) | | 0.16(6)+0.04x=(18+x) | | X-10=-5 | | 16y+8y-11y=91 | | 6c+4=22 | | 3x-16=1-2x | | 5(x+4)=7(w-2) | | x+15y=15 | | (2x-9)(x^2+5x-36)=0 | | 6s=42 | | -4y+4=-5y+1 | | 5x=95 | | 3p+4q=23 | | 2x=4+2 | | 6x^2+12xy+y^2+4x+7y+1=0 | | 7(x-3)+7=4x+3(-5+x) | | 12x+23y=395 | | 5n+13=3n-5 |

Equations solver categories